2016
DOI: 10.1039/c6ra05819a
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cu+ on ZnS:Cu p-type semiconductor films grown by sputtering: influence of substitutional Cu in the structural, optical and electronic properties

Abstract: ZnS:Cu films were synthetized by co-sputtering. A Cu content higher than 10.6 at% lead to changes as the shrinkage of the ZnS:Cu cell and development of a p-type behavior. These results are explained by the substitution of Zn+2 ions by Cu+ ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Low mobility of these materials are due to the high effective mass of holes. This was also corroborated via Seebeck coefficient measurements; representative data for the F4 with S = +35.5 µV K −1 , is shown in Fig.5.Chamorro et al also observed that for Cu > 10% content in RF sputtered Cu:ZnS, the film shows p-type conductivity[22]. From Fig.4, it can be seen that the conductivity…”
supporting
confidence: 62%
“…Low mobility of these materials are due to the high effective mass of holes. This was also corroborated via Seebeck coefficient measurements; representative data for the F4 with S = +35.5 µV K −1 , is shown in Fig.5.Chamorro et al also observed that for Cu > 10% content in RF sputtered Cu:ZnS, the film shows p-type conductivity[22]. From Fig.4, it can be seen that the conductivity…”
supporting
confidence: 62%
“…The p‐type conductivity is believed to come from the hole conducting network formed by CuS nanocrystals (p‐type) and it increases with the content of CuS, while the ZnS nano‐domains serve as the transparent fillers. Thus, it enables the nanocomposite film to possess both transparency and hole conductivity . Here, (CuS) 0.35 :(ZnS) 0.65 is chosen as the candidate to realize a p–n junction with n‐ZnO.…”
Section: Methodsmentioning
confidence: 99%
“…21 A significant step was development of a facile, low-temperature chemical bath deposition (CBD) approach, yielding ZnS:Cu y S composites with conductivities on the order of 10 3 S cm À1 , albeit with drops in transparency. 22 Subsequently, this compound has been synthesized via various chemical and physical methods, e.g., sol gel, 23 spray pyrolysis, 24,25 atomic layer deposition (ALD), 26,27 and sputtering, 28,29 among others (see Table S1). We emphasize that remarkable properties and crystalline films have been achieved even at low deposition temperatures; this is particularly advantageous to applications in optoelectronic devices with low thermal budgets, such as CdTe and perovskite photovoltaics (PV).…”
Section: Progress and Potentialmentioning
confidence: 99%
“…To contextualize our findings and highlight previous studies on this material, we compared properties of Cu x Zn 1Àx S reported in the literature in Figure 7. [19][20][21][22][23][24]28,37,[65][66][67][68][69] Marker shapes denote the phase reported in each study, which are all alloys except for the ZnS + CuS composite system (triangles), while the color indicates the reported Cu concentration. Samples from the literature are denoted with thin outlines, while those from this study have thick outlines.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation